2018
DOI: 10.1007/s11325-018-1718-3
|View full text |Cite
|
Sign up to set email alerts
|

Atypical sleep in critically ill patients on mechanical ventilation is associated with increased mortality

Abstract: The presence of atypical sleep and absence of normal PSG sleep characteristics in conscious critically ill patients on mechanical ventilation indicates involvement of sleep producing brain structures in the pathological process and is associated with poor outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Moreover, the lack of K-complexes or sleep spindles has been shown to be significantly associated with higher mortality in ICU patients. 108 Poor sleep quality is frequently named as one of the top stressors for ICU patients. [109][110][111][112] Light is the most critical external regulating factor of the circadian clock.…”
Section: Light the Role Of Light In Critical Illnessmentioning
confidence: 99%
“…Moreover, the lack of K-complexes or sleep spindles has been shown to be significantly associated with higher mortality in ICU patients. 108 Poor sleep quality is frequently named as one of the top stressors for ICU patients. [109][110][111][112] Light is the most critical external regulating factor of the circadian clock.…”
Section: Light the Role Of Light In Critical Illnessmentioning
confidence: 99%
“…K-complexes are generated in the cerebral cortex, and sleep spindles are generated by the reticular nucleus of the thalamus. 4,13 K-complexes and sleep spindles mark the transition from N1 to N2 sleep and suppress activation of the cortical networks involved in alertness. K-complexes and sleep spindles have been The absence of sleep spindles and K-complexes is associated with mortality.…”
Section: Changes In Non-rem and Rem Sleep In The Icumentioning
confidence: 99%
“…13,14 Researchers who examined the EEG characteristics of patients in the ICU during non-REM sleep reported that patients in the ICU may not demonstrate K-complexes and sleep spindles, and they found that the absence of K-complexes and sleep spindles was associated with an elevated mortality risk. 4 The inability to produce these EEG features could indicate dysfunction of the corticothalamic networks that generate these rhythms, which may be caused by brain injuries or the effects of ICU therapies and medications.…”
Section: Changes In Non-rem and Rem Sleep In The Icumentioning
confidence: 99%
“…It causes abnormalities in immune and metabolic endocrine functions, which play crucial roles in critically ill patients [ 4 , 5 ]. Additionally, it may be associated with the occurrence of delirium [ 6 ], noninvasive ventilation failure [ 7 ], and increased mortality [ 8 ]. Consequently, recent clinical guidelines have indicated the need for research methods to improve sleep [ 9 ].…”
Section: Introductionmentioning
confidence: 99%